Counseling of Work Program Student Study Service (SSN) in Sangkulirang District, Kutai Timur Regency - Eny Heriyati; Nursida Nursida; Aliri Aliri; Joni Ariansyah (Altifani Journal: International Journal of Community Engagement, 2023)
This Community Service (TCS) was carried out in 4 of the 15 villages in Sangkulirang District, East Kutai Regency. The province's main potential is capture fisheries, oil palm plantations and banana production. The purpose of this TCS is to spread knowledge and skills to the community through programs carried out by student study service (SSS). The TCS was carried out for two days, starting from Sempayau Village and Kolek Village on the first day, August 1th 2023. On the second day, August 2th 2023, it was carried out in Pulau Miang Village and Maloy Village. The method used is to hold discussions with local village officials, followed by briefing the work program of the student study service participants. Counseling work programs are selected based on the potential of each area. TCS activities in the four villages that were targeted for development through student TCS, were mainly on the socialization of product processing and demonstrations on how to process it. Most of the programs in each village are processing fishery and plantation products, making organic fertilizers, and practicing good product packaging methods. This TCS activity assists student study service students in directing village communities to develop diversification of processing and packaging methods so that they become products of higher value to the community.